Syair Sunur: Autobiografi seorang dagang Minangkabau - Suryadi, (Universiti Kebangsaan Malaysia, 2005)
This paper is a study of Syair Sunur, an autobiography in the form of syair. It was written by Syeikh Daud, a religious leader from Rantau Pariaman, in the west coast of Minangkabau in West Sumatra. The writer was born in Sunur, a coastal village close to Ulakan, center of Shâttariyah Sufi Order (tarekat), sometimes between 1785 and 1790. He died in about 1855 in Singkel, a port on the west coast of Aceh. The aim of this paper is not only to examine the handwritten copies as well as the print editions of SSn, but also to translite-rate one of them into Latin script and critically edit it. By doing so, it is hoped to be able to reconstruct the cultural and political context of Minangkabau, particularly Rantau Pariaman, as the backdrop of SSn to understand Syeikh Daud’s role in the context of Islamic modernist movement in Rantau Pariaman in the first half of the 19th Century